A Regularized Multi-Task Learning Approach for Cell Type Detection in Single-Cell RNA Sequencing Data - Upadhyay, Piu; Ray, Sumanta (Frontiers in Genetics, 2022)
Cell type prediction is one of the most challenging goals in single cell RNA-sequencing (scRNA-seq) data